2017
DOI: 10.2174/1874325001611010554
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Acetabular Labral Reconstruction with Fascia Lata Allograft: Clinical Outcomes at Minimum One-Year Follow-Up

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The postoperative mHHS for each study is shown in Figure 2. Additionally, 6 studies (2 allograft 3,25 and 4 autograft 1,7,14,24 ) provided sufficient data to conduct a meta-analysis comparing pre- versus postoperative mHHS scores (Figure 3). The random effects pooled mean difference in the mHHS, based on these 6 studies and a total of 315 patients, was an improvement of 29.0 points (95% CI, 20.2-37.8; P < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…The postoperative mHHS for each study is shown in Figure 2. Additionally, 6 studies (2 allograft 3,25 and 4 autograft 1,7,14,24 ) provided sufficient data to conduct a meta-analysis comparing pre- versus postoperative mHHS scores (Figure 3). The random effects pooled mean difference in the mHHS, based on these 6 studies and a total of 315 patients, was an improvement of 29.0 points (95% CI, 20.2-37.8; P < .0001).…”
Section: Resultsmentioning
confidence: 99%
“…Six meta-analysis or systematic reviews have been published in the last few years, alone, and point to equivalent or improved results with labral reconstruction compared to repair (Table 1) [7][8][9]11,17,18]. Likewise, at least 17 studies have been published within the last decade evaluating various outcomes of arthroscopic labral reconstruction using allograft [4,5,9,10,[12][13][14]16,[19][20][21][22][23][24][25][26][27] and autograft [28][29][30][31][32][33][34][35][36] techniques (Table 2). Overall, current evidence has concluded that arthroscopic labral reconstruction of the hip is associated with improved pain and functional status, low rates of complications or need for revision surgery, and rare progression of arthritis.…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Labral reconstruction using the tensor fascia lata was described by Rathi and Mazek [14] in 2017. The benefit of this graft choice is the versatility of the graft in terms of adjusting the grafts diameter (Fig.…”
Section: Tensor Fascia Lata Allograftmentioning
confidence: 99%
“…Anchors are used to secure the graft to the acetabular rim, taking care to avoid gaps between the native labrum and the graft. Rathi and Mazek [14] reported mHHS improvements from 58 (55–60) preoperatively to 95 (91–98) postoperatively at mean follow-up of 23 months (range: 16–36 months).…”
Section: Tensor Fascia Lata Allograftmentioning
confidence: 99%